Management of exaggerated gag reflex in dental patients using intravenous sedation with dexmedetomidine - Aleksei P Reshetnikov; Anton A Kasatkin; Aleksandr L Urakov; Dmitrii Y Baimurzin (Wolters Kluwer Medknow Publications, 2017)
Pharmacological sedation is one of the effective ways of prevention of gag reflex development in patients experiencing anxiety and fright before dental treatment. We are reporting a case where we could successfully eliminate exaggerated gag reflex (intravenous [IV] Gagging Severity Index) in a dental patient using IV sedation with dexmedetomidine. IV administration of dexmedetomidine provided elimination of gag reflex at a depth of sedation for the patient with the Richmond Agitation-Sedation Scale score of −2 and −1. The patient received dexmedetomidine 1.0 μg/kg for 10 min and then a continuous infusion of dexmedetomidine 0.4 μg/kg/h. The use of dexmedetomidine for sedation may be an alternative to other pharmacological agents in patients with dental anxiety accompanied by exaggerated gag reflex.